Lucas y Lucas ; El rapto de Caballo Gris - Mateos, Pilar; Lucini, Carmen (Madrid : Ediciones SM, 1998)
In Lucas y Lucas, Lucas is thinking what fun it would be if the Lucas in the mirror could come out. In El rapto de Caballo Gris, Donato is alone and bored one afternoon when the dorbell rings and the voice on the other says, "I am el Caballo Gris."
"Premio Lazarillo 1982."
"A partir de 9 anos"--P. [4] of cover.
Keywords: Mirrors -- Juvenile fiction; Horses -- Juvenile fiction; Mirrors -- Fiction; Horses -- Fiction